Obtaining stabilized enzymes and their application in the food industry - Toxirov, Baxtiyor Baxshilloyevich; Tagaeva, Mukhayo Bafoevna; Shukurova, Shakhina (Science and Education, 2023)
The article describes the traditional technological method for the production of cognacs and alcoholic beverages with the participation of immobilized enzymes, based on the fact that the resulting immobilized enzymes are stable in an organic environment. In addition, the article provides recommendations for reducing the amount of alcohol in alcoholic beverages using immobilized invertase and esterase enzymes to convert them into alkyl fructosides and esters.